Analisis Pengetahuan Masyarakat dalam Menghimpun Dana Infaq Studi Kasus: Motivasi Dalam Pembangunan Masjid Al-Mubarak (Jl. Mh Thamrin Kabupaten Bone, Sulawesi Selatan) - Rahayu, Rika; Firdaus, Muhammad; Hasbi, Hartas (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study examines how to analyze public knowledge in collecting infaq funds, using the case study of Al-Mubarak Mosque. The research employs a descriptive qualitative method with primary and secondary data. The results indicate that Al-Mubarak Mosque has implemented a transparent and accountable infaq fund management system. However, challenges remain in terms of communication and outreach to the community. Despite using donation boxes, information has not been effectively conveyed to all congregants and the surrounding community. Furthermore, there is a gap in understanding regarding infaq fund management among the public. To address this, we recommend improving communication strategies, utilizing online media, educational programs, transparency, and collaboration with related institutions. By implementing these recommendations, Al-Mubarak Mosque can enhance the effectiveness of its infaq fundraising programs, build public trust, and ensure that the collected funds are used effectively to advance the mosque and the surrounding community.